Beda Pengaruh Antara Senam Hamil Dengan Kompres Hangat Dan Massage Terhadap Penurunan Nyeri Punggung Bawah Pada Ibu Hamil Trimester III - Alloya, Ardiana, Wahyuni, M.Kes (2016)
Background : Changes in musculoskeletal system often causing pregnant women to feel pain in the lower back region. Growing of uterus affect the center of gravity, stretches out and weakness of the abdominal muscle, change posture and apply pressure on the back. This will lead to lower back pain in pregnant women. Objective : To understand the difference between the influence of pregnancy exercise with warm compress and massage to reduction of lower back pain in pregnant women Methods : This research method using Quasi Experimental research design with pre and post test with control group design. To compare pre and post test result using the Wilcoxon Test, while to compare the effect between pregnancy exercise with warm compresses and massage using Mann Whitney Test. Result : The result of this study shown that there is effect of pregnancy exerciseto reducing lower back pain in third semester pregnant women with score of p value 0,038<0,05, as of Ho is declined and Ha is accepted, which means there isbefore and after effect of pregnancy exercise. It show that pregnancy exercise proven effective reducing lower back pain with average 6,8 to 5,4. Result for giving warm compress and massage proven effective reducing lower back pain with average 7,2 to 3,6. This means there is difference between control group with pregnancy exercise and sample group with warm compress and massage.